CRAFTING THE PERSONA OF A HERO IN LITERARY COMPOSITIONS - Rustamov Ilkhom Tursunovich (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article investigates the craft involved in shaping the persona of a hero within literary compositions. It examines the diverse methodologies and approaches utilized by authors to construct engaging and memorable heroic figures that establish a connection with their audience. Through a thorough examination of pertinent literature and critical discussions, this research endeavors to explore the determinants influencing the evolution of heroic characters and their consequential role in molding the storyline and thematic underpinnings of literary works.